2018
DOI: 10.1016/j.visres.2017.02.008
|View full text |Cite
|
Sign up to set email alerts
|

The effects of monocular training on binocular functions in anisometropic amblyopia

Abstract: Intensive monocular perceptual learning can improve visual acuity, contrast sensitivity, and vernier acuity in the amblyopic eye in adults with amblyopia. It is however not clear how much monocular training can enhance binocular visual functions. In the current study, we aimed to evaluate effects of monocular training on a variety of binocular functions. Nineteen anisometropic amblyopes (18.5±1.26yrs, mean±s.e.) were trained in a grating contrast detection task near each individual's cutoff spatial frequency f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 69 publications
1
36
1
2
Order By: Relevance
“…Amblyopia is inherently a binocular disorder caused by an imbalance between the two eyes and resulting in the abnormal development of the visual pathways that affect both the amblyopic and the non-amblyopic fellow eye 25 . Anisohyperopic amblyopia is an important risk factor for amblyopia 5, 6, 7, 8, 9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amblyopia is inherently a binocular disorder caused by an imbalance between the two eyes and resulting in the abnormal development of the visual pathways that affect both the amblyopic and the non-amblyopic fellow eye 25 . Anisohyperopic amblyopia is an important risk factor for amblyopia 5, 6, 7, 8, 9.…”
Section: Discussionmentioning
confidence: 99%
“…After the prescription of refractive correction, occlusion therapy has been accepted as the second stage of the standard treatment for anisometropic amblyopia 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26. The general efficacy of part-time and full-time occlusion therapy according to the severity of amblyopia for best treatment outcomes has been established 11, 25, 27, 28…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies have tried to answer this question but have come to opposing conclusions: Chen et al (2016) found that monocular PL improved binocular combination in adult amblyopes. However, by using a similar training protocol, Jia et al (2018), failed to find any significant effect of monocular PL on binocular phase combination. Considering that the training in these two studies was conducted at a high spatial frequency (cutoff spatial frequency), which was not matched with the spatial frequency of their interocular suppression measurements (0.3 or 1 c/ • ), it would be necessary for further studies to explore the effect of PL on binocular visual functions using an approach (Kwon et al, 2015;Birch et al, 2016;Wang et al, 2019) that would allow the effect of spatial frequency to be considered for suppression.…”
Section: Relevance To Other Monocular Interventions In Amblyopiamentioning
confidence: 94%
“…A pesar de constituirse en un desorden intrínsecamente binocular, es tratado con la oclusión, la cual impide restaurar completamente los déficits generados por esta condición. Lo anterior permite replantear un enfoque que, al reducir la supresión, impacte directamente en la mejoría de la funciones visuales, mas no suponer que la agudeza visual obtenida con la oclusión estimule la visión binocular (9,10).…”
Section: Tratamientounclassified
“…Durante décadas, el tratamiento de referencia de esta alteración ha sido la oclusión del ojo dominante, de manera que todos los estímulos se derivan al ojo ambliope (8). Sin embargo, la ambliopía es intrínsecamente un desorden bi nocular (9), puesto que la presencia de los factores que generan una experiencia anormal en el desarrollo temprano de la visión afecta no solo la vía visual del ojo ambliope, sino también la del ojo sano (9). Por lo anterior, en la última década surge la idea de estimular la corteza visual con una terapia binocular a través de videojuegos basados en un principio dicóptico, que consiste en la presentación de imágenes distintas a cada ojo con el fin de equiparar el contraste y eliminar la supresión.…”
Section: Introductionunclassified